Chelate compounds and their use for correction of trace element deficiencies in livestock (review) - A. G. Koshchaev; N. E. Gorkovenko; A. V. Kosykh; D. V. Antipova (Ветеринария сегодня)
Livestock and poultry diseases occurring due to mineral or vitamin deficiencies are widely reported and belong to the factors restraining the development of livestock industry. Almost until the 90s of the last century, the conditions associated with trace element deficiency were prevented and treated using inorganic compounds. In recent decades, scientists have synthesized chelate metal compounds using organic carriers, determining the high bioavailability of these compounds and the efficiency that repeatedly exceeds the efficiency of inorganic compounds. Amino acids are preferably used as organic carriers. In addition to their main function, i.e. replenishing the trace element deficiency, chelate compounds increase the enzymatic activity, the functional activity of the immune system, and are also able to enhance the absorption of other trace elements, showing a synergistic effect. Due to the immunostimulatory activity resulting from increase in the content of sialic acids, properdin, ceruloplasmin, gamma globulin protein fraction, the metal chelates (copper, cobalt, iodine) can be used as immune response modulators. Iron chelate compounds are used for therapy and prevention of iron deficiency anemias not only in veterinary, but also in human medicine. This paper is based on data analysis of Scopus, CyberLeninka, PubMed, RSCI and other databases and systematizes scientific knowledge on the problem of designing and synthesizing metal chelate compounds using organic carriers. The scientific rationale is given for the use of amino acids and organic acids as organic carriers of metal, vitamin and other compounds. The mechanism of biological action of chelate compounds and the pathogenesis of trace element deficiencies in animals are considered, while the advantages of chelate compound use in microelementoses therapy and prevention are specified.